PSYCHOLOGICAL CHARACTERISTICS OF STUDENTS’ TYPES DEFINED BY CORRESPONDENCE BETWEEN THEIR INTEGRATED PERSONALITY AND INDIVIDITY ATTRIBUTES - Podshyvailov, Fedir; Podshyvailova, Lidia; Shepeliova, Maria (PSYCHOLOGICAL JOURNAL, 2020)
The performed theoretical analyses allowed us to define the attributes of a personality as a social display of a person, and the attributes of an individity as a social display of an individual. The personality attributes are: 1) sociability; 2) curiosity; 3) empathy; 4) creative curiosity; 5) aesthetic sensibility (as conscientious sociability); 6) sensitive empathy; 7) creativity; 8) sensitivity; 9) conscientious. The attributes of individity are: 1) psychotism; 2) mental imbalance; 3) disinhibition; 4) dominance tendency (as a neurotic psychotism); 5) depression (as an emotional insensibility of mental imbalance; 6) risk inclination; 7) emotional insensibility; 8) asociality; 9) neuroticism. In addition, the integral indicator of personality is aesthetic sensibility, and the integral indicator of individity is depression. The generalized analyses of the performed empiric research on modern students’ peculiarities allowed us to define students’ types depending on correspondence between their integral personality and individity attributes. Four types were distinguished: I type «+ +» (31,8%) consists of students with high aesthetic sensibility and deep depression (named “Avatarity”); II type «– +» (17,4%) consists of students with low aesthetic sensibility and deep depression (named “Individity”); III type «– –» (25,2%) includes students with low aesthetic sensibility and slight depression (conditionally named “Vitality”); IV type «+ –» (25,6%) consists of students with high aesthetic sensibility and slight depression (actually the “Personality” type). Basing on the revealed differences between students by the correspondence of their aesthetic sensibility and depression, we presented the extended characteristic of each type with the studied psychological indicators describing the above mentioned attributes (dispersion analyses and U-criterion of Mann-Whitney was uses). Thus, the I type is characterized by: neuroticism, conscientious, introversion, imagination, abulia (as a psychotic neuroticism), sensitivity (and its lower order component– femininity), mental imbalance, shyness, psychotism. The II type is characterized by: psychotism, mental imbalance, dominance tendency, emotional insensibility, neuroticism. The III type is characterized by: psychotism, mental imbalance, sensitive empathy, femininity, sociability (and its lower order component – general activity), sensitivity, shyness, conscientious, neuroticism. The IV type is characterized by: sociability (and its lower order component– general activity), sensitive empathy, creativity (and its lower order components – complexity and imagination), sensitivity (and its lower order component – femininity), conscientious.